226k views
1 vote
PLS HURRY!!
Simplify.
7/3+3(2/3−1/3)^2 Enter your answer in the box.

2 Answers

1 vote

Use order of operations (PEMDAS):-

7/3+3(2/3−1/3)^2 Deal with parentheses first:-

= 7/3 + 3 * 1/3^2 now exponent:

= 7/3 + 3 * 1/9 now the multiplication:-

= 7/3 + 3/9

= 7/3 + 1/3

= 8/3 Answer


User Luis Arteaga
by
5.3k points
4 votes

Do distributed property 7/3+3(2/3-1/3)^2 7/3+3×(2/3-1/3)^2 7/3+3×(1/3)^2 7/3×3×1/9 7/3×1/3 7+1/3 8/3 or 2 and 2/3 or 2.66667

User Bpinhosilva
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.